STRATEGI IKATAN MAHASISWA MUHAMMADIYAH DALAM PEMBENTUKAN KARAKTER MAHASISWA KOMISARIAT MUHAMMAD ABDUH - Hamidah, Rana Nur; Salim, Hakimuddin (PAI RAFAH, 2024)
The Muhammadiyah Student Association is an autonomous organization that provides cadre contributions to the Muhammadiyah Association. IMM, The Islamic student movement, operates in the field of religious, social, and student affairs. This research aims to describe and determine the role of the Muhammadiyah Student Association in forming the character of commissariat student Muhammad Abduh at the Muhammadiyah University of Surakarta. In anticipating and improving the character of children, one of them is through character education in schools (formal education). Character or personality education must be socialized, counseling, and intensive from an early age in all groups of the nation's life. The organization is also a series of activity processes that must be carried out to increase the relevance of all sources and aspects that ensure the success of the first management process by observing functions and movements in order to achieve predetermined goals. This research uses a qualitative descriptive approach with data collection methods through several techniques, namely literature or references, both journals and books. From the results of observation, interviews, and documentation, there are results that the character formation of students at the Muhammad Abduh commissariat begins with teaching the basic Tricometency ideology, namely intellectualism, religiosity, and humanity. So that it can form sensitive students. Forming character through habits or routines in IMM. Apart from that, it is also through activities such as the honesty canteen, social service, orphanage, the splendor of Ramadhan, tarjih school, and the blessing of Ramadhan